2021
DOI: 10.35787/jimdc.v10i2.487
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Incidental Carcinoma in Thyroids Operated for Multinodular Goiter

Abstract: Background: Multinodular goiter (MNG) is a common disease in Pakistan. However, malignancy can be found occasionally on histopathological examination of resected goiter specimens. The objective of this study was to determine the frequency of malignant lesions on histopathological examination in thyroid specimens operated for multinodular goiter.Material and Methods: A total of 154 patients undergoing thyroid surgery with preoperative diagnosis of multinodular goiter (MNG) at Al Nafees Medical College and Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Many national and international authors also reported the same finding for age. Zahid et al reported the mean age of 36±10 years in his study in Azad Kashmir 20 . Ito and his fellows conduct a research in Japan and documented the age of 50years 18 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Many national and international authors also reported the same finding for age. Zahid et al reported the mean age of 36±10 years in his study in Azad Kashmir 20 . Ito and his fellows conduct a research in Japan and documented the age of 50years 18 .…”
Section: Discussionmentioning
confidence: 88%
“…Patients presented with thyroid nodule are evaluated for thyroidectomy on the basis clinical history, fine needle aspiration cytology (FNAC) with or without ultrasound guidance 17 . But upon histopathological examination or immunohistopathological examination, the papillary carcinoma of thyroid was also reported as incidental finding along with MNG 20 .…”
Section: Discussionmentioning
confidence: 99%